2005
DOI: 10.1029/2005ja011207
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind control of the radial distance of the magnetic reconnection site in the magnetotail

Abstract: [1] To understand magnetotail dynamics, it is essential to determine where magnetic reconnection takes place in the near-Earth magnetotail during substorms. The Geotail spacecraft thoroughly surveyed the near-Earth plasma sheet at radial distances of 10-31 R E during the years 1995-2003. Thirty-four clear reconnection events were identified using the criterion of strong electron acceleration. Various solar wind parameters prior to each reconnection event were examined in order to find the factor controlling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
161
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 109 publications
(179 citation statements)
references
References 48 publications
18
161
0
Order By: Relevance
“…Miyashita et al [2004] used observations of the tail magnetic field variations during substorms to show that the initial reconnection site of intense substorms (i.e., category 1) tends to be located closer to Earth than that of weaker events (i.e., category 3). Nagai et al [2005] also showed that substorms occurring with stronger or more efficient solar wind energy input (i.e., category 1/2) have their onset location closer to Earth than those with weaker driving (i.e., category 3). The size of the energetic particle injection seen at geosynchronous orbit (and at any fixed observing position) is due to a combination of the particle acceleration (which moves the relatively higher fluxes of low-energy particles to higher energies) and particle transport (which determines whether these higher fluxes of high-energy particles encounter the observer).…”
Section: Solar Wind Drivingmentioning
confidence: 99%
“…Miyashita et al [2004] used observations of the tail magnetic field variations during substorms to show that the initial reconnection site of intense substorms (i.e., category 1) tends to be located closer to Earth than that of weaker events (i.e., category 3). Nagai et al [2005] also showed that substorms occurring with stronger or more efficient solar wind energy input (i.e., category 1/2) have their onset location closer to Earth than those with weaker driving (i.e., category 3). The size of the energetic particle injection seen at geosynchronous orbit (and at any fixed observing position) is due to a combination of the particle acceleration (which moves the relatively higher fluxes of low-energy particles to higher energies) and particle transport (which determines whether these higher fluxes of high-energy particles encounter the observer).…”
Section: Solar Wind Drivingmentioning
confidence: 99%
“…However, these studies used Geotail data obtained during the solar minimum. Nagai et al [2005] compared solar wind parameters prior to reconnection onset in the near tail (À25 R E < X GSM < Figure 21. Same as Figure 12 but for the time interval 0805 UT until 0825 UT for P3.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The THEMIS-B data in our survey was taken in 2009 during solar minimum. It is possible that MMS will encounter more diffusion regions during solar maximum (Nagai et al 2005). But even if we double the number of estimated magnetotail diffusion region candidates to 30, with each event lasting on average 30 minutes (which includes not only the diffusion region but also the exhausts on both sides of the X-line) all the burst data of can be transmitted to ground during a 6-month tail season, with 75 % of the telemetry still available for capturing other phenomena.…”
Section: Diffusion Region Candidatesmentioning
confidence: 99%